Information support for the procedure of power consumption planning in the municipal water supply system (Моделювання, керування та інформаційні технології, 2019)
The article deals with the issue of determining theenergy baseline of municipal water supply facilities, taking intoconsideration their actual operation conditions. The purpose ofthe article is to develop the principles of organization ofinformation support for the procedures of power consumptionplanning and their integration into the energy managementsystem. The formalization of the power consumption planningprocess has been performed based on the object-orientedtechnology. Classes that take into account the characteristics ofthe facility, water consumption, methods of planning watersupply and power consumption have been formed. Description ofthe properties and methods of the classes has been accomplished.The architecture of the information support system for planningprocedures has been proposed. WEB-oriented technologies hasbeen suggested to use for information exchange. This allowscreating a single information space, taking into consideration theactual operation conditions of the research object.